Administration of sildenafil citrate not able to reduced hs-CRP on erectile dysfunction patient at Doctor Soetomo Hospital, Surabaya, Indonesia - I Gusti Ngurah Pramesemara; Rossy Sintya Marthasari; Rezia Octarina; Ahmad Ricardo Syukur Silalahi; Judie Hartono; Tjahjo Djojo Tanojo (Intisari Sains Medis, 2019)
Background: Phosphodiesterase type-5 (PDE5) inhibitors was the first choice for the oral treatment of erectile dysfunction because of its ability to prevent endothelial dysfunction and restored erectile function properly. However, the inflammatory parameter such as hs-CRP can be used to assess the performance of PDE5 inhibitors as well as clinical questionnaires, IIEF-5, and EHS. So that, this study aims to determine the effect of PDE5 inhibitors administration such as sildenafil citrate 50 mg per day can decrease the value of hs-CRP, as well as increased the IIEF-5 and EHS at Dr. Soetomo General Hospital.Methods: A true clinical experimental studies used pretest and posttest control group design were carried out among 20 patients during 4 weeks. In the next 2 weeks, the crossover was conducted among respondents for the washout period whereas divided into 2 groups, control (K1 and K2) and treatment (P1 and P2). Data were analyzed using Statistical Package for the Social Sciences (SPSS) version 16.0 software for Windows.Results: The average age of group K1 and P2 was 51 Â± 12.07 years old whereas 48.60 Â± 15.40 years old in group P1 and K2. The research was conducted in Andrology Clinic of Doctor Soetomo Hospital in Surabaya during June to November 2017. The research data were not normally distributed, then analyzed by two-tail T-group tests and Wilcoxon test at significance level Î±=0.05. The results showed that PDE5 inhibitors did not decrease the hs-CRP significantly (p>0.05), but increased EHS (p<0.05) and increased IIEF-5 (p<0.05) significantly.Conclusion: This study concluded that the administration of sildenafil citrate per day by oral increased the EHS and IIEF-5, but not able to reduced hs-CRP in patients with erectile dysfunction significantly.